Profil Darah dan Pertumbuhan Ikan Patin (Pangasius sp.) Pada Pemeliharaan menggunakan Sistem Microbubble dan Tanpa Microbubble - idrus, idrus; Lembessy, Salnida Yuniarti; Satyono, Bagus Dwi Hari (Jurnal Media Akuakultur Indonesia, 2024)
The study aims to analyze the influence of microbubbles on the blood profile and growth of patin fish (Pangasius sp.) on the maintenance using microbobble and without microbulble systems. The research was carried out for 50 days in the round pool of the Aquatic Crop Studies Program, Faculty of Agriculture, University of Mataram using a complete random design (RAL) consisting of 2 treatments and 20 repetitions namely P1: cultivation with microbubble technology and P2: cultivation without microbobble technology. Test parameters include hematocrites, haemoglobin, erythrocytes, leukocyte differentials, absolute weight, longitude, specific weight, length, feed conversion ratio (FCR), feeding efficiency (EPP), survival (SR) and water quality. The data were analyzed using the Student t non-parametric statistical test using the SPSS program. Research results show that the use of microbubbles can enhance growth, SGR, FCR, and EPP of better patin fish (Pangasius sp.) with still optimal blood profiles.